Interactive scenario generation for mission‐based virtual training. (14th May 2013) - Luo, Linbo; Yin, Haiyan; Cai, Wentong; Lees, Michael; Zhou, Suiping
ABSTRACT: For a virtual training system, how to effectively and quickly generate training scenarios has become a challenging issue. A scenario generation system is needed to produce scenarios that can meet different objectives and at the same time be customized for individuals. In this paper, we introduce a scenario generation framework for mission‐based virtual training, which aims to generate scenarios from both trainer and trainee's perspective. The framework allows a trainer to direct the scenario generation process, so that the generated scenarios reflect the trainer's preferences over different mission objectives. It also considers how the scenarios could adapt to different trainees' skill levels. The representation of scenario beat is proposed, and the scenario generation process adopts a combinatorial optimization approach generating the sequence of scenario beats. The efficacy of the proposed framework is demonstrated through an empirical study of human players in a simple food distribution mission game. The results show that a trainee can achieve better performance improvement when playing the customized scenarios tailored to the trainee's skill level as compared with the uncustomized scenarios. Copyright © 2013 John Wiley & Sons, Ltd.